REGULARIZATION OF PARTIALLY INTEGER VECTOR OPTIMIZATION PROBLEMS WITH QUADRATIC CRITERIA - Lebedeva, Т.Т.; Semenova, N.V.; Sergienko, T.I. (Reports of the National Academy of Sciences of Ukraine, 2024)
The article is devoted to the question of regularization of partially integer Pareto-optimization problems with vector criterion input perturbations. New results are obtained for the case when the vector problem is partially integer with quadratic functions as criteria. The developed regularization procedure is based on the use of the Slater stability property with respect to perturbations of criterion coefficients of the vector optimization problem. The obtained results - the conditions of stability to possible perturbations of vector criterion input data and the developed procedure of regularization of vector optimization problems — are related to the solution of problems of correct modeling of economic, ecological, technological, social processes in conditions of effective accounting of incompleteness and uncertainty of input information.